Arrangement of high molecular weight associated proteins on purified mammalian brain microtubules (The Rockefeller University Press, 1977)
The arrangement of the high molecular weight proteins associated with the walls of reconstituted mammalian brain microtubules has been investigated by electron microscopy of negatively stained preparations. The images are found to be consistent with an arrangement whereby the high molecular weight molecules are spaced 12 tubulin dimers apart, i.e., 960 A, along each protofilament of the microtubule, in agreement with the relative stoichiometry of tubulin and high molecular weight protein. Molecules on neighbouring protofilaments seem to be staggered so that they give rise to a helical superlattice, which can be superimposed on the underlying tubulin lattice. In micrographs of disintegrating tubules there is some indication of lateral interactions between neighbouring high molecular weight molecules. When the microtubules are depolymerized into a mixture of short spirals and rings, the high molecular weight proteins appear to remain attached to their respective protofilaments.